Relationship between HbA1c with Hypoglycaemic Attack and Diabetic Complications of Patients Admitted in a Tertiary Hospital - Nath, Jishu Deb; Biswas, Rajat Sanker Roy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Hypoglycemia is a major complication of diabetes mellitus and common causes of admission in hospital. Those who have long duration of diabetes having poor glycemic control, frequently experienced such events were self treated at home. The present study pointed to identify whether hemoglobin A1c (HbA1c) a marker of average plasma glucose, relates with severe hypoglycemia and diabetic complications or not. Materials and methods: A retrospective observational study was conducted in the Department of Medicine, Maa-Shishu-O-General Hospital, Agrabad, Chattogram from April 2019 to September 2021. Total 36 patients were selected, as presenting in Medicine Department with documented hypoglycaemia. All data was taken meeting exclusion criteria and analysed. Results: Hypoglycaemic episodes mostly occurred in elder cases (>61 year of ages) n=16, 44% and HbA1c mostly belongs to between 7.6 to 8 groups. Confusion is the most common presentation, N=63, 63.9%. Neuropathy was found as common complication, (30.6% , n=11) cases and most of the neuropathy found in HbA1c 7.6 to 8.5 groups 54.54% , n=6 . Most of the patients were taking sulfonylurea group of drugs 47.2% , n=17, and mixed acting insulin n=21 ,58.3%. Conclusion: Hypoglycemic admission is not related to extensive Diabetic control rather with related to elder patients , various Diabetic complications and injudicious use of ant diabetic agents. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 44-47